2005
DOI: 10.1103/physrevb.72.100503
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbon for superconductivity inMgCxNi3from specific heat

Abstract: The influence of carbon deficiency on superconductivity of MgCNi 3 is investigated by specific heat measurements in the normal and superconducting state. In order to perform a detailed analysis of the normal state specific heat, a computer code is developed which allows for an instantaneous estimate of the main features of the lattice dynamics. By analyzing the evolution of the lattice vibrations within the series and simultaneously considering the visible mass enhancement, the loss in the electron-phonon coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…On the one hand, ab-initio calculations rapidly showed that the electronphonon coupling constant (λ e−ph ∼ 0.2) is far too low to account for the high critical temperatures observed in oxypnictides (up to ∼ 55 K) and an unconventional mechanism mediated by the SF associated with a sign reversal of the (s-wave) order parameter between electrons and holes sheets of the Fermi surface has been proposed [10]. On the other hand, it has been suggested that the narrow van Hove singularity could be responsible for a nearly unstable phonon mode in MgCNi 3 inducing a large, although reduced by SF, λ e−ph [11,12] in agreement with experiments which yield an average electronphonon coupling constant in the order of 1.7 [11,13,14]. The interplay between electron-phonon coupling and SF is further emphasized in this system by the existence of a large isotopic effect [15] which has been suggested to be enhanced by the strong SF [16].…”
supporting
confidence: 54%
See 1 more Smart Citation
“…On the one hand, ab-initio calculations rapidly showed that the electronphonon coupling constant (λ e−ph ∼ 0.2) is far too low to account for the high critical temperatures observed in oxypnictides (up to ∼ 55 K) and an unconventional mechanism mediated by the SF associated with a sign reversal of the (s-wave) order parameter between electrons and holes sheets of the Fermi surface has been proposed [10]. On the other hand, it has been suggested that the narrow van Hove singularity could be responsible for a nearly unstable phonon mode in MgCNi 3 inducing a large, although reduced by SF, λ e−ph [11,12] in agreement with experiments which yield an average electronphonon coupling constant in the order of 1.7 [11,13,14]. The interplay between electron-phonon coupling and SF is further emphasized in this system by the existence of a large isotopic effect [15] which has been suggested to be enhanced by the strong SF [16].…”
supporting
confidence: 54%
“…On the other hand, the Hall probe has been placed close to the center of the sample in the HPM measurements and is hence sensitive to the bulk of the sample. In the case of MgCNi 3 , it is known that the critical temperature has a surprising high sensitivity to a very small change in the C or Ni stoechiometry [4,20] and also surface stress [14,38]. Assuming that the critical temperature of the surface is 20 % smaller than the bulk value, very good fit to the data could be obtained for ρ T DO S using Eq.1 for T < 3 4 T c (still taking ∆(0) = 2k B T c , see solid lines in Fig.…”
mentioning
confidence: 99%
“…They considered small m sp = 0.1, and obtained much reduced T c = 11.5 K even in the case of Θ D = 300 K. Spin-fluctuation is responsible for that higher value (3.02) of λ, due to excess amount of Carbon [38]. The difference in experimental and fitted electronic specific heat data (C es /γT) [see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Quite recently, two important investigations were carried for this system. It was deduced from the specific heat measurements [60] that in a carbon-deficient sample low-energy nickel phonon modes (which are probably the most important in superconductivity) were shifted to higher energies. Furthermore, electronic structure calculations performed for MgC x Ni 3 in the range 0.80 < x < 1 exhibited the decrease of n(E F ) with the increasing x [61], but less drastic than in our Sc 3 XB x systems.…”
Section: B Effect Of Vacancy On B-sitementioning
confidence: 99%